2004
DOI: 10.1177/089686080402400509
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Oral Ciprofloxacin in Continuous Cycling Peritoneal Dialysis

Abstract: Background In order to avoid aminoglycosides, the International Society for Peritoneal Dialysis recommends cefazolin and ceftazidime for empirical treatment of peritonitis. Ciprofloxacin covers relevant gram-negative pathogens without the resistance associated with ceftazidime. However, ciprofloxacin pharmacokinetic data in patients on continuous cycling peritoneal dialysis (CCPD) are lacking. Objectives ( 1 ) To determine the pharmacokinetics of oral ciprofloxacin in CCPD patients, ( 2 ) to compare serum and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Oral administration of fluoroquinolones is commonly used alone or in combination with other antibiotics ( 237 ). Oral ciprofloxacin and moxifloxacin reach adequate levels within the peritoneum ( 293 , 323 ). However, adequate IP levels may require a day to be reached, and some oral phosphate binders can bind fluoroquinolones and reduce their bioavailability ( 324 , 325 ).…”
Section: Initial Presentation and Management Of Peritonitismentioning
confidence: 99%
See 1 more Smart Citation
“…Oral administration of fluoroquinolones is commonly used alone or in combination with other antibiotics ( 237 ). Oral ciprofloxacin and moxifloxacin reach adequate levels within the peritoneum ( 293 , 323 ). However, adequate IP levels may require a day to be reached, and some oral phosphate binders can bind fluoroquinolones and reduce their bioavailability ( 324 , 325 ).…”
Section: Initial Presentation and Management Of Peritonitismentioning
confidence: 99%
“…Vancomycin can probably be given intermittently for APD patients. Oral ciprofloxacin can also achieve adequate levels within the peritoneum in APD patients ( 323 ). In a retrospective, single-center observational cohort study of 508 episodes of PD-associated peritonitis in 208 patients, no differences in relapse rates, mortality, or the combined end-point of mortality and catheter removal were observed between APD and CAPD patients continuing their own PD modality during continuous IP antibiotic treatment in each PD exchange, although elevated dialysis effluent leukocyte counts and antibiotic treatment durations were longer in the former ( 90 ).…”
Section: Initial Presentation and Management Of Peritonitismentioning
confidence: 99%
“…The Committee recommends center-specific selection of empiric therapy, dependent on the local history of sensitivities of organisms causing peritonitis ( Opinion ). Gram-positive organisms may be covered by vancomycin or a cephalosporin, and gram-negative organisms by a third-generation cephalosporin or aminoglycoside ( Evidence ) (Figure 1) (65-105).…”
Section: Specimen Processingmentioning
confidence: 99%
“…There were plenty of pharmacokinetics studies about cipro oxacin after a single dose oral administration of a cipro oxacin tablet in adult patients or healthy subjects, but most of studies on the pharmacokinetics of cipro oxacin mainly focused on the dose of 500 mg, the studies about a single dose of 250 mg were rare among them [14,[24][25][26][27][28][29][30][31][32][33]. Several previous studies indicated that the 250-mg singledose of cipro oxacin was e cacious and safe in the therapy of uncomplicated gonorrhea,equally to the 500-mg dose of cipro oxacin [7,[34][35][36][37], so it's meaningful to investigate the pharmacokinetics of a single dose of cipro oxacin 250 mg.…”
Section: Discussionmentioning
confidence: 99%